Fishery management in a marine protected area with compliance gaps: Socio-economic and biological insights as a first step on the path of sustainability. (15th February 2021) - Coppa, Stefania; Pronti, Andrea; Massaro, Giorgio; Brundu, Roberto; Camedda, Andrea; Palazzo, Luca; Nobile, Giorgio; Pagliarino, Elena; de Lucia, Giuseppe A.
Abstract: Overfishing is one of the main impacts on the marine environment and multiple-use Marine Protected Areas (MPAs) could be a useful tool to conserve biodiversity and promote sustainable resource exploitation. However, ensuring a high level of protection on the ground is a difficult task. This work contributes to the analysis of the causes at the root of MPAs' ineffectiveness by examining the management of Paracentrotus lividus fishery in an Italian MPA, employing a multidisciplinary approach built on biological and socio-economic competences. This sea urchin species has a determinant ecological role in structuring infralittoral benthic assemblages and is the most exploited echinoid in Europe. From 2010 to 2018, underwater sampling was conducted over 39 monitoring sites to define P. lividus spatial and temporal trends. Declared catches and semi-structured interviews with local stakeholders were used to define the socio-economical context, underline existing conflicts among them, as well as to trace the historical evolution of sea urchin fishery. The results show that the management of sea urchin fishery is not sustainable, primarily because of the stakeholders' non-compliance with the rules. P. lividus stock is progressively declining (−73% in 9 years), showing no difference between MPA (0.5 ± 0.15 ind./m 2 ) and control sites (0.3 ± 0.04 ind./m 2 ). Moreover, fishermen dominate the social arena while scientists, civil society and local press have little relevance. Additionally, the untruthfulness of catch declarations was proved, the IUU fishery is relevant and the black market is hiding the actual economic value. This work offers management solutions that may be useful in other areas that show similar compliance issues. Highlights: Multidisciplinary research is key in examining fishery sustainability in an MPA. Regulatory capture and coordination issues limit the institutions' effectiveness. IUU fishing and the black market hide the real economic value of sea urchin fishery. Stock decreased by 73% in 9 years and unreported catches compelled its management. Short and long-term actions with feedback controls can fix compliance gaps.